2005
DOI: 10.1111/j.1365-2664.2005.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Life after logging: post‐logging recovery of a neotropical bat community

Abstract: 1.There is considerable debate about whether tropical forests can be managed for timber production and to conserve biodiversity. Few 'sustainable forestry' systems have been evaluated adequately in this respect. Microchiropteran bats may be model taxa for this purpose. They are an important component of mammalian diversity, play key roles in forest dynamics and are indicators of disturbance in neotropical forests. 2. We investigated the effect of Trinidad's periodic block system (PBS) on bat species diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
2
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 40 publications
8
62
2
10
Order By: Relevance
“…Compared with studies conducted in systems with a low fragment-matrix contrast, the observed magnitude of responses was, as hypothesized, often greater, probably as a result of the particular nature of the matrix. Gleaning animalivores, as in other studies (Fenton et al, 1992;Sampaio, 2000;Clarke et al, 2005), were the most adversely affected ensemble, with markedly reduced abundance or complete absence on the islands. Causes for this fragmentation sensitivity may include insufficient resources in fragments, i.e.…”
Section: Assemblage Patternssupporting
confidence: 66%
“…Compared with studies conducted in systems with a low fragment-matrix contrast, the observed magnitude of responses was, as hypothesized, often greater, probably as a result of the particular nature of the matrix. Gleaning animalivores, as in other studies (Fenton et al, 1992;Sampaio, 2000;Clarke et al, 2005), were the most adversely affected ensemble, with markedly reduced abundance or complete absence on the islands. Causes for this fragmentation sensitivity may include insufficient resources in fragments, i.e.…”
Section: Assemblage Patternssupporting
confidence: 66%
“…Conclusiones generales: A pesar de la importancia del sesgo inducido por los muestreos (Voss & Emmons, 1996;Simmons & Voss, 2001;Meyer et al, 2011), el problema de la detectabilidad no es considerado explí-citamente en la gran mayoría de estudios de variación espacial en abundancia, presencia y riqueza de murciélagos (Medellín et al, 2000;Clarke et al, 2005;Castro-Luna et al, 2007;Willig et al, 2007;Avila-Cabadilla et al, 2009). Sin embargo, los resultados del presente estudio muestran que existen una considerable variación en detectabilidad relacionada con variaciones entre gremios tróficos y tipos de cobertura, lo cual está de acuerdo con previos estudios que han evaluado las fuentes de variación relacionadas con la detectabilidad de murciélagos tropicales (Meyer et al, 2011).…”
Section: Riqueza De Especies De La Comunidad De Murciélagosunclassified
“…Nuestros resultados concuerdan con estudios previos que ha reportado que las comunidades de murciélagos despliegan fuertes respuestas a la pérdida de bosque y al cambio en el uso de la tierra (García-Morales, Badano & Moreno, 2013;Medellín et al, 2000;Clarke et al, 2005;Castro-Luna et al, 2007;Willig et al, 2007;Avila-Cabadilla et al, 2009). Los resultados de las capturas también concuerdan con una serie de meta-análisis, en los cuales se comparó la frecuencia de presencia de especies de murciélagos entre bosques bién preservados y áreas utilizadas por humanos, y se encontró que en general las áreas utilizadas por humanos contienen más especies de murciélagos que los bosques bien preservados (García-Morales et al, 2013).…”
Section: Riqueza De Especies De La Comunidad De Murciélagosunclassified
See 1 more Smart Citation
“…exhibited the greatest response; this was likely explained by preferences for less-cluttered, open space, and by species-specific food and cover requirements. The lack of response to many forest characteristics suggests that non-Phyllostomid aerial insectivorous bats in this study may be less sensitive to changes in forest structure and composition than Phyllostomids [24,[32][33][34][35], or that the relationships need to be examined at finer taxonomic levels, and that, at this level, they may not be as useful as indicators of alteration [13][14][15]. Further, these species may have some tolerance for disturbance and change, such as the hurricanes and selective logging experienced in the CFR and possibly to changes in forest structure and composition associated with climate change.…”
Section: Discussionmentioning
confidence: 92%